A Tool to Measure the Attitude of Farmers Toward Conservation Agriculture - Saji, Sherin Maria; Mallappa, Vinaya Kumar Hebsale; Rathwa, Minal (Indian Journal of Extension Education, 2023)
When assessing farmers’ predispositions and developing a strategy for extension work in the region, the attitude of farmers toward conservation agriculture is a crucial consideration. The purpose of this study was to develop a valid and reliable instrument for assessing farmers’ attitudes toward conservation agriculture. The scale product method is used to construct the scale. It is a hybrid of the Likert and Thurstone techniques. The study was conducted in March 2022. On a 5-point scale, 65 judges evaluated 25 statements. Finally, 18 statements including 14 positive statements and 4 negative statements were chosen to build a scale that would assess the attitude of farmers towards conservation agriculture. The scale was found reliable, with the reliability coefficient (r) (Guttman split-half Coefficient and Spearman-Brown Coefficient Equal Length) determined to be 0.917. The scale’s validity was evaluated using expert judgement. Employing the scale in research will aid in knowing farmers’ attitudes about conservation agriculture.
Keywords: Attitude; Conservation agriculture; Guttman split-half coefficient; Reliability; Validity; Scale product method